Koombana Bay plaques - Whish-Wilson, David (2018)
Commissioned by the City of Bunbury – 10 x 600 word plaques written in consultation with Bunbury’s Noongar community. These plaques are on permanent exhibition across the Koombana Bay foreshore redevelopment - inscribed steel plates with text and images mounted on jarrah.